Collaborative school leadership in a global society: A critical perspective. (September 2019) - Woods, Philip A; Roberts, Amanda
In the context of evolving global challenges and opportunities, this article explores the kind of leadership that moves beyond the philosophy of dependence which pervades many of the everyday assumptions of educational leadership practice. The article argues for educational leadership that places relational freedom, self-determination, and critical reflexivity as the driving aim of distributed leadership by teachers, students and others in non-positional leadership roles. A project arising from the International Teacher Leadership initiative is examined in order to offer practical illustration.